Human Resources and Local Revenue Optimization: Insights from a Phenomenological Inquiry - Susilowati Susilowati; Diyah Probowulan; Abadi Sanosra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study explores how human resources (HR) interpret and perform their strategic roles in optimizing Local Own-Source Revenue (PAD) at the Regional Revenue Agency (Bapenda) of Bondowoso Regency. PAD plays a significant role in supporting regional fiscal independence, yet its achievement relies heavily on employee competence, work motivation, digital readiness, and collaboration across institutions. Using a phenomenological approach, the research captures the lived experiences of internal actors (Bapenda employees) and external stakeholders such as taxpayers, partner institutions, and local government units. Data were collected through in-depth interviews, observations, and document reviews, and analyzed using coding techniques. The findings reveal seven central themes: HR competency, training and development, motivation and incentives, digital capability, collaboration, regulatory constraints, and managerial innovation. The study highlights that PAD optimization requires not only technical proficiency but also adaptive behavior, communication effectiveness, and supportive organizational and regulatory environments. This research provides practical insights for improving HR management in regional revenue institutions and contributes to a deeper understanding of the human-centered aspects of public-sector revenue performance